Penguatan dan Pemahaman Kimia Melalui Learn Management System (LMS): Teachmit pada MGMP Kimia Kabupaten Bantul - Febriana, Beta Wulan; Hidayat, Habibi; Merdekawati, Krisna; Arlianty, Widinda Normalia; Wiyantoko, Bayu; Fajarwati, Febi Indah; Yanti, Ika (LPPM IST AKPRIND Yogyakarta, 2024)
This activity is a training activity on strengthening understanding of chemistry through the Learning Management System (LMS). The basis for taking this activity is based on a needs analysis that has been carried out for the MGMP Chemistry teacher in Bantul Regency. A needs analysis was conducted using non-test instruments in the form of open questionnaires and interviews. Based on the needs analysis results, it shows that most teachers experience problems implementing online learning activities so that learning materials cannot be delivered properly. The method used in this activity is formal socialization—offline. The material presented is related to chemistry and applications and the introduction of LMS. LMS: Teachmint is considered to be able to facilitate students and teachers in teaching and learning activities. Teachers can efficiently conduct video conferences, share material in the form of files/videos, provide deadlines for collecting assignments, and assess and even interact with students using only a single platform. This training received a positive response from chemistry teachers; most teachers agreed to use the platform in chemistry learning